Development of Latvian-English‑Latvian Dictionaries of Legal Terms (1991–2017) - Karpinska, Laura (Baltic Journal of English Language, Literature and Culture, 2018)
The study presents an insight into the development of the Latvian-English and English-Latvian dictionaries of legal terms published in Latvia since regaining of independence in 1991 when the need of the English language grew dramatically in comparison with the Soviet period. Bilingual dictionaries of legal terms help to establish terminological equivalents, but this task is more difficult if both languages are linked to different legal systems, for instance, the common law and civil law system as it is in the case of English and Latvian. The aim of this study is to give an insight into the development of the Latvian-English-Latvian dictionaries of legal terms published in Latvia since regaining of independence. The lexicographic material selected for analysis comprises the five dictionaries of legal terms published in this period. The analysis focuses on such aspects of the dictionaries as their volume, target user group, complexity of entry structure and uniformity of dictionary structure. The analysis reveals some typical features of the Latvian-English-Latvian dictionaries of legal terms as well as their development that is related to increase in the number of headwords, complexity of the microstructure and lexicographic solutions applied in order to tackle the problem of non-equivalence.